Differential Inhibition of APOBEC3 DNA‐Mutator Isozymes by Fluoro‐ and Non‐Fluoro‐Substituted 2′‐Deoxyzebularine Embedded in Single‐Stranded DNA. (19th December 2019) - Kvach, Maksim V.; Barzak, Fareeda M.; Harjes, Stefan; Schares, Henry A. M.; Kurup, Harikrishnan M.; Jones, Katherine F.; Sutton, Lorraine; Donahue, John; D'Aquila, Richard T.; Jameson, Geoffrey B.; Harki, Daniel A.; Krause, Kurt L.; et al.
Abstract: The APOBEC3 (APOBEC3A‐H) enzyme family is part of the human innate immune system that restricts pathogens by scrambling pathogenic single‐stranded (ss) DNA by deamination of cytosines to produce uracil residues. However, APOBEC3‐mediated mutagenesis of viral and cancer DNA promotes its evolution, thus enabling disease progression and the development of drug resistance. Therefore, APOBEC3 inhibition offers a new strategy to complement existing antiviral and anticancer therapies by making such therapies effective for longer periods of time, thereby preventing the emergence of drug resistance. Here, we have synthesised 2′‐deoxynucleoside forms of several known inhibitors of cytidine deaminase (CDA), incorporated them into oligodeoxynucleotides (oligos) in place of 2′‐deoxycytidine in the preferred substrates of APOBEC3A, APOBEC3B, and APOBEC3G, and evaluated their inhibitory potential against these enzymes. An oligo containing a 5‐fluoro‐2′‐deoxyzebularine (5FdZ) motif exhibited an inhibition constant against APOBEC3B 3.5 times better than that of the comparable 2′‐deoxyzebularine‐containing (dZ‐containing) oligo. A similar inhibition trend was observed for wild‐type APOBEC3A. In contrast, use of the 5FdZ motif in an oligo designed for APOBEC3G inhibition resulted in an inhibitor that was less potent than the dZ‐containing oligo both in the case of APOBEC3GCTD and in that of full‐length wild‐type APOBEC3G. Abstract : Design of ssDNAs as inhibitors of A3 enzymes with the aid of chemically modified nucleosides : Incorporation of 5‐fluoro‐2′‐deoxyzebularine into single‐stranded DNA in place of the target dC residue yielded more powerful inhibition of APOBEC3A and APOBEC3B—but not of full‐length APOBEC3G—than that observed with the non‐fluorinated 2′‐deoxyzebularine.